The Relationship of Serum 25-Hydroxyvitamin D Concentrations with Mortality among the Patients Diagnosed with the Cardiovascular Diseases - Naveeda Nawaz, Tayyaba Batool, Saba Arif, Maria Sarfraz, Rabbia Shabbir, Saira Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Serum 25-Hydroxyvitamin D is a biomarker used to assess an individual’s vitamin D status. Bone health, immune function, calcium and phosphate metabolism is crucially regulated by the vitamin D. Cardiovascular diseases (CVD) are the leading cause of death world widely. Many studies have shown that the vitamin D plays potential role cardiovascular diseases prevention. Study design: It is a prospective study conducted at Rawal Institute of health sciences, Islamabad for the duration of six months from July 2022 to December 2022. Material and Methods: The review board committee of the hospital approved the study. In the given study, a total of 300 patients were selected. All these patients were included in this study according to the inclusion criteria. The statistical analysis was conducted. The multivariable Cox regression analysis was done. The immunoassays analyzer was used for vitamin D status assessment. Results: The average age of the patients were ranging from 56 to 63 years and all of them were suffering from cardiovascular diseases. Different patterns like qualification, educational history with regard to awareness, Smoking patterns, Diabetic medications, and duration of cardiovascular diseases were considered in this study. Conclusion: Serum 25-hydroxyvitamin D concentrations and all-cause mortality are inversely related. The risk of all-cause mortality is lower in the participants with higher serum 25-hydroxyvitamin D concentrations than those with lower concentrations. Keywords: Hydroxyvitamin D and cardiovascular diseases.